2008
DOI: 10.1038/sj.bjc.6604503
|View full text |Cite
|
Sign up to set email alerts
|

High-risk human papillomavirus infections in breast cancer in Syrian women and their association with Id-1 expression: a tissue microarray study

Abstract: High-risk human papillomaviruses (HPVs) could be important risk factors for breast carcinogenesis and metastasis. Based on this hypothesis, we recently studied the effect of E6/E7 onco-proteins of high-risk HPV type 16 in two non-invasive human breast cancer cell lines, BT20 and MCF7; we reported that E6/E7 converts these cell lines to invasive cells. This is accompanied by an overexpression of Id-1, which is an important regulator of breast metastasis. In this investigation, we examined the presence of highri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
123
2
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 32 publications
(25 reference statements)
19
123
2
10
Order By: Relevance
“…Previous studies have demonstrated the presence of HPV high-risk types 16, 18 and 33 in breast cancer specimens from diverse populations around the world: Italy, Norway, China, Japan, USA, Austria, Brazil, Australia, Taiwan, Turkey, Greece, Korea, Mexico, Hungary and Syria (Lonardo et al, 1992;Hennig et al, 1999;Yu et al, 1999;Liu et al, 2001;Damin et al, 2004;Widschwendter et al, 2004;de Villiers et al, 2005;Kan et al, 2005;Tsai et al, 2005;Gumus et al, 2006;Kroupis et al, 2006;Lawson et al, 2006;Choi et al, 2007;Akil et al, 2008;Khan et al, 2008;Kulka et al, 2008;MendizabalRuiz et al, 2009). The prevalence of HPV positive breast cancer in these studies was reported to vary from 4% in Mexican to 86% in American women.…”
mentioning
confidence: 99%
“…Previous studies have demonstrated the presence of HPV high-risk types 16, 18 and 33 in breast cancer specimens from diverse populations around the world: Italy, Norway, China, Japan, USA, Austria, Brazil, Australia, Taiwan, Turkey, Greece, Korea, Mexico, Hungary and Syria (Lonardo et al, 1992;Hennig et al, 1999;Yu et al, 1999;Liu et al, 2001;Damin et al, 2004;Widschwendter et al, 2004;de Villiers et al, 2005;Kan et al, 2005;Tsai et al, 2005;Gumus et al, 2006;Kroupis et al, 2006;Lawson et al, 2006;Choi et al, 2007;Akil et al, 2008;Khan et al, 2008;Kulka et al, 2008;MendizabalRuiz et al, 2009). The prevalence of HPV positive breast cancer in these studies was reported to vary from 4% in Mexican to 86% in American women.…”
mentioning
confidence: 99%
“…6 Herein, we report that high-risk HPVs type 45, 51, 52 and 58 are frequently present in colorectal cancer in this population (p < 0.001, p < 0.001, p < 0.001 and p < 0.0001, respectively) ( Table 1), in some cases multiple types of HPV infections were detected. Therefore and based on previous studies, [6][7][8] and our present data on colorectal cancer, we conclude that the most frequent high-risk HPV types, in the Syrian population, are 16, 33, 35, 45, 52 and 58 (Table 1). In parallel, it is important to mention that our preliminary data of HN cancers in the Syrian population show that 43% of these cancers are positives for high-risk HPVs; while, genotyping of high-risk HPVs is presently under investigation by our group, we believe that data of this analysis will be similar to our data of cervical and colorectal cancers (Ghabreau et al, in preparation).…”
Section: Does the Syrian Population Have To Wait For The New Generatimentioning
confidence: 97%
“…However, a new generation of broad spectrum HPV vaccines, protecting against multiple high-risk HPV types is emerging. At present, a phase III trial is running to assess the carcinomas in the Syrian population, [6][7][8] we firmly believe that the new generation of high-risk HPVs vaccine will present the best protection for the Syrian people against HPV viruses. This great advancement could reduce the development of cervical, colorectal, breast and HN cancers by more than 50%, as well as decrease their progression to a metastatic form which is responsible for the majority of cancer-related deaths.…”
Section: Does the Syrian Population Have To Wait For The New Generatimentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente se conocen bien varios factores de riesgo asociados con el cáncer de mama, pero en la mayoría de las mujeres afectadas no es posible identificar ningún factor en particular relacionado con el desarrollo de la enfermedad 3 . En las últimas décadas se ha considerado como factor importante en el desarrollo de cán-cer la acción de un grupo de virus que provocan tumores, tanto en modelos experimentales como en humanos 4,5 . El virus del papiloma humano (VPH) es el agente etiológico del cáncer de cuello uterino, y el virus de Epstein-Barr (VEB) está asociado principalmente con el carcinoma nasofaríngeo y el linfoma de Burkitt.…”
Section: Introductionunclassified